In silico Test Proteolytic Potential of Papain and Zingibain Enzymes Against Protein Forming Congenital and Senilis Cataracts - Gangsar Lintas Damai; Nugraha Wahyu Cahyana; Ayu Munawaroh Aziz (Journal of Agromedicine and Medical Sciences, 2022)
Abstract Phacoemulsification is cataract therapy’s gold standard with lowest complication rate and best visual outcome. However, phacoemulsification is expensive and difficult to use widely. Pathogenesis of cataract related to Crystalline P23T γD protein in congenital cataracts and β-amyloid protein in senile cataract. Papain enzymes and zingibain enzymes are cataract’s alternatives therapy with proteolytic effects that potentially lyse these proteins. Proteolytic injection with 30-gauge needle results in small, safe incision. Papain enzyme from Carica Papaya plant and zingibain enzyme from Zingiber Officinale plant which grows plentifully in Indonesia that becomes cheap source of proteolytic. This study’s purpose is to compare probability of binding energy based on Binding Interaction Model (BIM) between papain and zingibain enzymes against Crystalline P23T γD protein and β-amyloid protein with molecular docking. This research uses https://cluspro.bu.edu./login.php. BIM with lowest binding energy has most stable bond. Docking results show interaction probability between papain enzyme and Crystalline P23T γD protein has lowest binding energy of -730.4 kJ/mol at BIM 1. Probability of interaction between papain enzyme and β-amyloid protein has lowest binding energy of -697.2 kJ/mol at BIM 1. Probability of interaction between the enzyme zingibain and the crystalline P23T protein γD has lowest binding energy of -890.5 kJ/mol at BIM 2. Probability of interaction between the enzyme zingibain and the β-amyloid protein has lowest binding energy of -873.5 kJ/mol at BIM 0. It was concluded that the zingibain enzyme has the most stable probability of forming a stable bond to Crystalline P23T γD protein and β-amyloid protein. Keyword:In silico, papain, zingibain, cataract